1978
DOI: 10.1085/jgp.72.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of veratridine on Ca fluxes and the release of oxytocin and vasopressin from the isolated rat neurohypophysis.

Abstract: A B S T R A C T Uptake of radioactive calcium, 4~Ca efflux, and hormone release from the isolated rat neurohypophysis were monitored in vitro after the addition of veratridine to the incubation medium. Veratridine dramatically increased hormone release, but the release rate was not sustained and had declined by about 90% after 2 h. Removal of external Na § prevented hormone release as did addition to the incubation medium of tetrodotoxin or the calcium antagonists D600 and Mn z+ ions. Veratridine increased 45C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 15 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…Vasopressin release in our system (at 9 Hz) was abolished in the presence of tetrodotoxin, the blocker of sodium channels (Narahashi, Moore & Scott, 1964), or in the absence of calcium ions from the superfusion medium. Thus, we feel justified to infer that the hormone release occurred following an action potential-induced, calcium-dependent secretary mechanism similar to that thought to occur in vivo (Nordmann & Dyball, 1978).…”
Section: Discussionmentioning
confidence: 84%
“…Vasopressin release in our system (at 9 Hz) was abolished in the presence of tetrodotoxin, the blocker of sodium channels (Narahashi, Moore & Scott, 1964), or in the absence of calcium ions from the superfusion medium. Thus, we feel justified to infer that the hormone release occurred following an action potential-induced, calcium-dependent secretary mechanism similar to that thought to occur in vivo (Nordmann & Dyball, 1978).…”
Section: Discussionmentioning
confidence: 84%
“…An increase in sodium permeability in the presence of sodium would be expected to depolarize the plasma membrane and increase calcium entry through a potentialsensitive channel. Veratridine increases 45Ca incorporation into islets (Donatsch et al 1977) and posterior pituitary (Nordmann & Dyball, 1979) and to a lesser extent into anterior pituitary cells. Moreover, with the exception of Donatsch et al (1977), all the groups have reported that veratridine does not increase secretion in the absence of external calcium, and this is also the case for bovine growth hormone release.…”
Section: Discussionmentioning
confidence: 92%
“…It seems reasonable to conclude that the increase in 22Na content of bovine pituitary cells exposed to veratridine is due to the opening of a voltage-sensitive sodium channel. Veratridine has also been shown to stimulate release of insulin (Donatsch et al 1977;Pace, 1979), posterior pituitary 1c00 hormones (Nordmann & Dyball, 1979) and catecholamines (Ito et al 1979). In each case stimulation of secretion was prevented by tetrodotoxin and, when it was investigated, by sodium removal.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations